Model Lanskap Permukiman Tradisional Masyarakat Adat Rejang Provinsi Bengkulu Berbasis Budaya Lokal - Putra Liantono; Andi Gunawan; Indung Sitti Fatimah (Jurnal Lanskap Indonesia, 2024)
Rejang is one of the original tribes of Bengkulu Province. This tribe mostly lives in the Bukit Barisan area. Some of their settlements are undergoing changes due to the rapidly growing flow of information and communication today. Conservation efforts need to be made, especially about their traditional settlement landscape model. The purpose of this study is to identify and analyze the character of traditional settlement landscapes and their constituent elements and compile a model of traditional settlement landscapes of the indigenous Rejang people. This research uses a descriptive method through a literature study approach, interviews, and field observations. The analysis was carried out descriptively and spatially. The landscape character of the indigenous Rejang tribe settlement is in the form of hilly landforms with land cover in the form of forests, gardens, and terraced rice fields, with the valley floor in the form of small and medium rivers. Traditional settlements stretch over ridges to mountain peaks. The character-forming features of landscapes include both natural and artificial features. Natural features consist of the elements of hills, forests, and rivers. Artificial features consist of terraced rice fields, gardens/fields, and settlements. The settlement itself includes traditional houses (including traditional chiefs' houses), circulation paths, public open spaces, and tombs. The elements that make up the Residential Garden include residential houses, rice barns (tangkiang), kitchens, fence plants, vegetable and flower plants, trees, yards, mortar (places to pound rice). Traditional ceremonial activities are held inside and outside the home, as well as communal activities such as planting and harvesting rice held in rice fields. The landscape model of the traditional settlement of the indigenous people of Rejang Lebong is linear with the center of the settlement along the main road on the ridge. The settlement is surrounded by gardens/fields and rice fields. The forest is on the outside away from settlements.